Chaos surviving machinery - Montenegro Joo, Javier (2014)
Usually the machinery used in engineering applications, especially those implicating cyclic processes make use of oscillating systems that include components vibrating each one with a particular frequency, in a medium with continuously changing muffling, temperature, etc. As a consequence these vibrations may eventually break the harmony of the common oscillation and experiment chaos. Hence some Chaos notions are critical in this type of applications. This work reports the results of a chaos research in a very frequently applied oscillating system. It is found that chaos is an eventual occurrence. After the system undergoes chaos, it returns to its oscillating stage under the conditions imposed by the medium (muffling, temperature, frequency, etc.) at the moment of leaving chaos. This leads to considering the eventual design of chaos surviving machinery